Penerapan Analisa SWOT dan AHP dalam Perencanaan Strategi Pemasaran Kopi Bubuk PDP Kahyangan Jember - Naning Retnowati; Dhanang Eka Putra (Jurnal Ilmiah Inovasi, 2018)
This paperÂ  employs combination of SWOT analysis and Analytic Hierarchy Process (AHP) in strategic marketing planning for powdered coffee product in PDP Kahyangan Jember. SWOT analysis identified internal and external factors which are prioritized by expert in marketing strategy by means of AHP. Results indicate that cost advantage, market expansion and material management were the best marketing strategy that could have been implemented. Â